Chapter 31 The End of a Golden Era of British Music? Exploration of Educational Gaps in the Current UK Creative Industry Strategy - Boehm, Carola (Taylor & Francis, 2019)
The creative industries, and particularly our UK Music industry, are perceived as healthy, resilient and strong. However, with the ongoing policy changes in secondary and higher education, as well as the continued cuts to council budgets and the ongoing lack of commitment to wealth distribution and even investment in the whole nation, this golden era of the creative industries in the UK may not last. In my latest articles, I explore critical themes relevant for the UK Music industry and the UK creative sector as a whole. Current national policy expressions often omit to address these themes, which are necessary to safeguard our future creative resilience. In writing this article, much relevance will be drawn from making connections to recent public debates on what universities are for and what their role is within the creative economy. Attention is given to considering current governmental industry strategies critically and their relevance for the music industry, together with their sector responses.